Adequate vitamin D level associated with reduced risk of sporadic colorectal cancer - Ma, Yanhui; Deng, Lin; Huangfu, Yuchan; Zhou, Yunlan; Wang, Ping; Shen, Lisong (Frontiers in Nutrition, 2023)
Purpose: The effect of vitamin D level pertinent to colorectal cancer incidence, progression, or mortality risk is complicated, and study findings are mixed. We evaluated whether serum vitamin D (25-hydroxyvitamin D, 25(OH)D) is associated with the incidence of sporadic colorectal cancer (CRC). Methods: This study is a retrospective analysis of the relationship between serum 25(OH)D level and risk of CRC. Age, sex, body mass index, history of polyp, disease conditions (i.e., Diabetes), medications and other 8 vitamins were used as confounding factors. A total of 389 participants were enrolled in this study including 83 CRC patients without family history and 306 healthy controls between January 2020 and March 2021 at the Department of Colorectal Surgery and Endoscope Center at Xinhua Hospital, Shanghai Jiao Tong University School of Medicine. Adjusted smoothing spline plots, subgroup analysis and multivariate logistic regression analysis was conducted to estimate the relative risk between serum 25(OH)D and sporadic CRC risk. Results: After fully adjusting the confounding factors, it was found that circulating 25(OH)D played a protective role in patients with CRC (OR = 0.76 [0.63, 0.92], p = 0.004) and that an adequate vitamin D level was significantly associated with a reduced CRC risk compared to vitamin D deficiency or sufficiency (OR = 0.31 [0.11, 0.9], p = 0.034. According to the study, Statins did not affect the potential protective effects of vitamin D (OR = 1.02 [0.97, 1.08], p = 0.44) and may account for the inverse association between serum 25(OH)D and colorectal cancer. Conclusions: An adequate level of serum 25(OH)D was associated with a reduced CRC risk, especially for the elderly. The finding on the absence of vitamin D protective effect in Statins use subgroup, suggesting it may be one of substantial contributing confounders, warrants further investigation.